Exploring how Grade 11 Physical Science learners make sense of the concept of rates of reactions through the inclusion of the indigenous practice of making oshikundu: a Namibian case study - Nikodemus, Kristof Shingwilila (Rhodes University, Faculty of Education, Department of Education, 2017)
It has been observed that the teaching and learning of the concept of rates of reactions is seen as being difficult for most Namibian learners. Concerns have been expressed in Examiners' Reports about candidates showing little knowledge of the topic 'rates of reactions'. Hence, this study sought to explore how indigenous knowledge and practices through a practical activity of making oshikundu, enabled or constrained learner-engagement and sense-making of the concept of rates of reactions in Namibian schools. Underpinned by an interpretive paradigm, the study tried to describe and understand how learners make sense of their world. Within the interpretive paradigm, a mixed-method case study approach was adopted. It is informed by Vygotsky's socio-cultural theory, which recognises that learning and meaning-making are represented as originating from social interactions among individuals. The research study was conducted in a rural secondary school in the northern part of Namibia with Grade 11 Physical Science learners. Purposive sampling techniques were used to select three learners from the class, as the interview sample. A pre-test was used to gather data on the type of prior knowledge that Grade 11 Physical Science learners had of concepts related to rates of reactions. The pre-test's content was validated by two Physical Science specialists. Observations were used to explore how learners make sense of rates of reactions during lessons. In addition to observations, interviews and a post-test were used in order to gather data on how the practical activity of making oshikundu enabled or constrained Grade 11 Physical Science: (a) learner engagement and (b) sense-making of the concept of rates of reactions. The findings of the study found that learners were more engaged and participated more fully in class than in previous year when the indigenous practice of making oshikundu was incorporated during the science lessons. The study thus recommends that indigenous knowledge and practices be integrated into Physical Science classrooms for effective teaching and learning and sense making of science concepts.
Keywords: Uncatalogued